Punctuated evolution of canonical genomic aberrations in uveal melanoma - Matthew G. Field (Nature Portfolio, 2018)
Uveal melanoma (UM), the most common primary eye cancer, is strongly linked to mutations in the tumor suppressor BAP1. Here, the authors analyze 151 primary UM samples to find that BAP1 and other canonical genomic aberrations arise in an early punctuated burst followed by neutral tumor evolution.